Low-Temperature Specific Heats of the β′ and ζ 0 Phases in Equiatomic AgZn - Abriata, José Pablo; Bressan, Oscar José; Luengo, C. A.; Tholouze, D. (1970)
Fil: Abriata, J. P. Comisión Nacional de Energía Atómica; Argentina